2020
DOI: 10.7326/m20-0529
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Urine Protein–Creatinine Ratio or Urine Dipstick Protein to Urine Albumin–Creatinine Ratio for Use in Chronic Kidney Disease Screening and Prognosis

Abstract: ; for the Chronic Kidney Disease Prognosis Consortium ‡ Background: Although measuring albuminuria is the preferred method for defining and staging chronic kidney disease (CKD), total urine protein or dipstick protein is often measured instead. Objective: To develop equations for converting urine proteincreatinine ratio (PCR) and dipstick protein to urine albumincreatinine ratio (ACR) and to test their diagnostic accuracy in CKD screening and staging. Design: Individual participant-based meta-analysis. Setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
149
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 204 publications
(155 citation statements)
references
References 39 publications
1
149
0
5
Order By: Relevance
“… The 95% confidence intervals were calculated based on 10-fold cross-validation; DSP Scale 1: reported as Negative, Trace, 1 + , 2 + , 3 + , 4 + ; DSP Scale 2: reported as Negative, Trace, 10, 30, 100, 300, or ≥ 300; only the performance of the final pooled classifiers across Columbia University, University of Minnesota, and Vanderbilt University are summarized, for detailed breakdown of site-specific performance see Tables S1 – S5 , and for additional validation studies and comparisons with recently published methods by Sumida et al 24 , see Table S6 . …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… The 95% confidence intervals were calculated based on 10-fold cross-validation; DSP Scale 1: reported as Negative, Trace, 1 + , 2 + , 3 + , 4 + ; DSP Scale 2: reported as Negative, Trace, 10, 30, 100, 300, or ≥ 300; only the performance of the final pooled classifiers across Columbia University, University of Minnesota, and Vanderbilt University are summarized, for detailed breakdown of site-specific performance see Tables S1 – S5 , and for additional validation studies and comparisons with recently published methods by Sumida et al 24 , see Table S6 . …”
Section: Resultsmentioning
confidence: 99%
“…To further test our A-stage prediction, we compared the performance of our classifiers to the alternative methods developed more recently by the CKD Prognosis Consortium 24 (Supplementary Table 6 ). Based on an independent testing dataset, we demonstrated that the performance of the two methods was generally comparable.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the availability of an equation to convert protein-to-creatinine ratio to albumin-to-creatinine ratio makes the latter easier and cheaper to estimate. 42 Of note, although the protocol used in France to achieve albuminuria measurement cannot be implemented routinely, we can speculate that the use of standard protocols and laboratory test prescriptions managed by nurses may improve adherence to recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…The regression coefficient of diabetes to ACR was 2.4 times higher in comparison to PCR and 5.1 times higher in comparison with non-albumin proteins, in accordance with the concept that high albuminuria is a key marker of diabetic kidney dysfunction [ 43 ]. Moreover, the difference in the regression coefficients of diabetes with PCR and ACR indicated that the relation between PCR and ACR could differ between diabetics and nondiabetics [ 44 ]. Last, the inverse relation of serum 25(OH)-vitamin D with urinary ACR could reflect mechanism(s) similar to those proposed for anti-proteinuric effects of vitamin D supplementation [ 31 ].…”
Section: Discussionmentioning
confidence: 99%